Technology Trends Analysis Using Patent Landscaping - Kortov, Sergey Vsevolodovich; Shulgin, Dmitry Borisovich; Tolmachev, Dmitry Evgenyevich; Yegarmina, Anastasiya Dmitrievna (Economy of Regions, 2017)
The article is devoted to the analysis and the choice of the priorities in technology development and, particularly, to the use of patent landscaping as a tool for the study of technology trends. Currently, patent activity indicators are often used for technology foresight and for competitive intelligence as well. Nevertheless, causal relationship between these indicators, on the one hand, and strategic and tactical decisions in the sphere of technological development on meso- and microeconomic level, on the other hand, are not adequately investigated to solve practical tasks. The goal of the work is to systemize the challenges of technology trends analysis, which could be effectively solved on the base of patent landscape analysis. The article analyses the patent landscaping methodology and tools, as well as their use for evaluating the current competitive environment and technology foresight. The authors formulated the generalized classification for the criteria of promising technologies for a selected region. To assess the compliance of a technology with these criteria, we propose a system of corresponding indicators of patenting activity. Using the proposed methodology, we have analysed the patent landscape to select promising technologies for the Sverdlovsk region. The research confirmed the hypothesis of the patent landscapes performance in evaluating such technology indicators as stages of the life cycle stage, universality (applicability in different industries), pace of worldwide development, innovations and science availability in the region and potential possibilities for scientific collaboration with international research institutions and universities. The results of the research may be useful to the wide audience, including representatives small and medium enterprises, large companies and regional authorities for the tasks concerned with the technology trends analysis and technology strategy design.